Inisiasi Program Janji Temu Kader Dengan Ibu Hamil Sebagai Upaya Peningkatan Pemeriksaan Sesuai Jadwal Di Puskesmas Sungai Turak - Herlina Herlina; Meldawati Meldawati; Siti Noor Hasanah (Jurnal Pengabdian Ilmu Kesehatan, 2024)
The health problem of pregnant women is a public health problem that needs major attention because it has an impact on the quality of life and future generations. The risk of pregnancy is very likely to be experienced by a mother and must receive preventive, monitoring and treatment efforts as early as possible so as to contribute to reducing the causes of maternal morbidity and mortality. ANC or antenatal care is care for the mother and fetus during pregnancy. Through ANC, various information and education related to pregnancy and childbirth preparation can be provided to mothers as early as possible. Pregnant women in the Sungai Turak Community Health Center work area have various obstacles in relation to routine ANC checks, for example due to work, time opportunities, and family support in taking them to the Community Health Center. The proposed solution is the initiation of a cadre appointment program with pregnant women, where pregnant women who do not have the opportunity to have their pregnancy checked at the Puskesmas/Posyandu are contacted and make an appointment with cadres, then continue with the implementation of activities. The activities and results of the program implemented are leaflets which are used as outreach materials.